A minimization algorithm for equilibrium problems with polyhedral constraints. (3rd May 2016) - Cruz Neto, J.X.; Lopes, J.O.; Soares, P.A.
Abstract : Our aim in this paper is to study an infeasible interior proximal method for solving equilibrium problems with polyhedral constrains in a quasiconvex setting. Under mild assumptions, we show that the sequence generated by our algorithm is well defined and it converges to a solution of the problem when regularization parameters converge to zero.